1987
DOI: 10.3171/jns.1987.66.1.0047
|View full text |Cite
|
Sign up to set email alerts
|

Primary spinal melanoma

Abstract: The records of five patients with primary melanoma of the spinal cord were reviewed. The tumor most frequently presented as an intramedullary middle or lower thoracic cord lesion. The average duration of symptoms before pathological diagnosis was 29 months, and the average survival after laminectomy and radiation therapy was 6 years 7 months. The findings in this series, when compared with those in the literature, suggest that primary spinal melanoma is a more indolent malignancy than previously reported or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
74
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 5 publications
2
74
0
Order By: Relevance
“…In the case of metastatic melanoma of the spine it is usually indicative of a highly aggressive pathology; however primary melanoma tends to remain in the spine for a relatively extended period of time. Studies have shown that although cutaneous metastatic melanoma has a life expectancy of 6 months, patients with primary melanoma of the CNS can live up to 7 years after initial diagnosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of metastatic melanoma of the spine it is usually indicative of a highly aggressive pathology; however primary melanoma tends to remain in the spine for a relatively extended period of time. Studies have shown that although cutaneous metastatic melanoma has a life expectancy of 6 months, patients with primary melanoma of the CNS can live up to 7 years after initial diagnosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…20 On the other hand, it has been reported that primary spinal melanomas present a very di erent clinical course than those of the more common melanoma of the skin with metastases to the central nervous system, which is usually fatal within 6 months because of widespread metastases. In our case, the long duration of symptoms supports the opinion that primary spinal melanoma presents an indolent course.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, primary melanomas of the spinal cord seem to be associated with a longer survival than do those primarily situated in the brain, and may be associated with several years of survival after diagnosis. 6,20 The magnetic resonance characteristics of intracranial melanomas have been discussed by Uematsu et al, who reported a case of meningeal melanocytoma, showing homogeneous high intensity on the T1-weighted image and low intensity on the T2-weighted image. 5 Paramagnetic stable free radicals, such as indole semiquinones and semiquinonimines are present in melanocytic tumors causing a decrease in the T1 and T2 relaxation times.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of this lesion in the spinal cord is even rarer. [1][2][3] Magnetic resonance imaging features of melanoma are determinated by the degree of pigment melanin and the presence of acute or chronic hemorrhage and can be easily misdiagnosed with other central nervous system tumors. 2,3 The pathologic examination is critical for proper diagnosis.…”
mentioning
confidence: 99%
“…2,3 The pathologic examination is critical for proper diagnosis. We report case of primary spinal melanoma.…”
mentioning
confidence: 99%